Analisis Yuridis terhadap Perjanjian Kerjasama antara Petani Tembakau di Kabupaten Jember dengan PT. Adi Sampoerna - Supianto Supianto; Nanang Tri Budiman (Fakultas Hukum Universitas Islam Jember, 2017)
Legal protection by contracting in the business world is a very popular type. On the other hand, however, the extent of the opportunity to determine the protection of the law itself by contracting often leads to unexpected losses. The application of equitable legal protection principles in cooperation agreements, aims to protect the interests of the parties in relation to the regulation of their respective rights and obligations based on the principles of justice and legal certainty. The principles of law based on justice and certainty become the basis of the birth of cooperation agreement made by farmers with PT. Adi Sampoerna, in addition to other principles contained in the contract law. Object of study of this research is the science of normative law, then the method used is doctrinal which mengaranakan logic deduction.Cooperation agreement between tobacco farmers in Jember Regency and PT. Adi Sampoerna is a contract standard agreement. The principle of freedom of contract if faced with a contractual agreement, or agreement made by parties without the same bargaining position, it can be said that the cooperation agreement is not in accordance with the principle of freedom of contract even resulted in an agreement that unfair. Besides not in accordance with the principle of freedom of contract, there are several other legal principles of contract that are potentially violated, namely: good faith, existence and abuse of circumstances. A form of legal protection that can be done so that both sides are in a balanced position is to refer to the provisions of the inclusion of the standard clause as stipulated in Article 18 of the Law on Consumer Protection and does not include an exoneration clause that could harm either party in the agreement.